2022
DOI: 10.1212/wnl.0000000000201042
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Structural Findings in Patients With Lesion-Induced Dystonia

Abstract: Background and Objectives:Brain lesions are a well-recognized etiology of dystonia. These cases are especially valuable as they offer causal insight into the neuroanatomical substrates of dystonia. To date, knowledge of lesion-induced dystonia comes mainly from isolated case reports or small case series, restricting broader description and analysis.Methods:Cases of lesions-induced dystonia were first identified from a systematic review of published literature. Latent class analysis then investigated whether pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 45 publications
1
34
0
1
Order By: Relevance
“…Intersection of the cerebellum and pallidum verifies lesion sites identified in patients with secondary cervical dystonia. (9)(10)(11) Posteroventral GPi intersection supports the brainstems involvement in mediating therapeutic networks, given that this area of the pallidum is widely regarded as the DBS hotspot for cervical dystonia, and occupies somatotopic cervical territory. (15,73,74) The observed cortical motor fibre intersection corroborates the somatotopic head and neck areas, as the terminus of white matter tracts associated with optimal clinical motor symptom reduction, in cervical dystonia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Intersection of the cerebellum and pallidum verifies lesion sites identified in patients with secondary cervical dystonia. (9)(10)(11) Posteroventral GPi intersection supports the brainstems involvement in mediating therapeutic networks, given that this area of the pallidum is widely regarded as the DBS hotspot for cervical dystonia, and occupies somatotopic cervical territory. (15,73,74) The observed cortical motor fibre intersection corroborates the somatotopic head and neck areas, as the terminus of white matter tracts associated with optimal clinical motor symptom reduction, in cervical dystonia.…”
Section: Discussionmentioning
confidence: 98%
“…(7,8) Lesion-identification studies have identified spinal cord, basal ganglia, brainstem, cerebellum, and thalamic regions as most affected in patients with cervical dystonia, (9,10) with the brainstem and cerebellum as the most commonly affected regions in a recent study. (11) All lesion sites have been classified to ascertain connectivity with the cerebellum, (10) and surmounting evidence supports cerebellar involvement in dystonic sensorimotor pathophysiology. (7,8,(12)(13)(14) Brain-based imaging markers offer a potential avenue to explore variability in patients with cervical dystonia, in relation to therapeutic DBS outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Lesion network mapping studies associate focal CD with cerebellar and brainstem lesions, whereas limb dystonia is linked to basal ganglia lesions. 20,21 Contemporary dystonia theories highlight the significance of an abnormal neural network connecting the cerebellum, brainstem, basal ganglia, and cerebral cortex. Dysregulation in any part of this network can manifest as dystonia symptoms through a common pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Modern theories propose involvement of the cerebellum and brainstem, 11‐17 and CD patients with head tremors may also exhibit cerebellar ataxia 18,19 . Lesion network mapping studies associate focal CD with cerebellar and brainstem lesions, whereas limb dystonia is linked to basal ganglia lesions 20,21 …”
mentioning
confidence: 99%
“…Although cases of lesion-induced dystonia are rarer than those of isolated dystonia, they offer a unique opportunity to explore causal inferences between neuroanatomical structures and dystonia. In this issue of Neurology ®, Corp et al 5 identified 359 published cases of lesion-induced dystonia in a systematic review of published cases. By investigating the relationship between lesion location and phenotypic features of the dystonia, they ascertained that only half of the lesions were located in the basal ganglia, with other lesions commonly located in the cerebellum, brainstem, and white matter.…”
mentioning
confidence: 99%